PERSPEKTIF PELESTARIAN LINGKUNGAN HIDUP DALAM ISLAM - M. Syakur Sf. (Universitas Wahid Hasyim, 2008)
Promoting and appreciating Islamic religious spirituality is a condition sine qua non to keep its strength equal to that of natural law, economic law, and market mechanism over which none and no system could control. Nonetheless, leaving the economic law and market mechanism prevail uncontrolled is not an Islamic attitude of religious behavior. Authentic religious attitude and way of life must be prophetic and trans-formative in nature and manifested in the practical action of watching and controlling the development of the natural law and economic law themselves. Otherwise, human beings could be subordinated and co-opted by the natural law. Indeed, having firm religious traditions, Muslim communities are exercised to plead themselves from the shackling routines of daily life. There has to be a serious and continuous effort to understand fundamental and functional meaning of formal rituals of Islam, in such a way that Islam supports not only Theo-centric but also socio-economic concerns. Once Islam is shackled by its routines and finds no alternative interpretation of its rituals, there hardly is hope of important contributions made by Islamic scholars to cope with ecological and global crises. Kata-Kata Kunci: Lingkungan, Pembangunan, Etika dan Spiritual